Structure-activity relations of parasin I, a histone H2A-derived antimicrobial peptide - Koo, Young Sook; Kim, Jung Min; Park, In Yup; Yu, Byung Jo; Jang, Su A.; Kim, Key-Sun; Park, Chan Bae; Cho, Ju Hyun; Kim, Sun Chang (ELSEVIER SCIENCE INC, 2008)
The structure-activity relations and mechanism of action of parasin I, a 19-amino acid histone H2A-derived antimicrobial peptide, were investigated. Parasin I formed an amphipathic a-helical structure (residues 9-17) flanked by two random coil regions (residues 1-8 and 18-19) in helix-promoting environments. Deletion of the lysine residue at the N-terminal [Pa(2-19)] resulted in loss of antimicrobial activity, but did not affect the a-helical content of the peptide. The antimicrobial activity was recovered when the lysine residue was substituted with another basic residue, arginine ([R-1]Pa), but not with polar, neutral, or acidic residues. Progressive deletions from the C-terminal [Pa(1-17), Pa(1-15)] slightly increased the antimicrobial activity (1-1 mu g/ml) without affecting the a-helical content of the peptide. However, further deletion [Pa(1-14)] resulted in nearly complete loss of antimicrobial activity and a-helical structure. Confocal microscopic analysis and membrane permeabilization assays showed that parasin I and its analogs with comparable antimicrobial activities localized to the cell membrane and subsequently permeabilized the outer and cytoplasmic membranes. Pa(1-14) also localized to the cell membrane, but lost membrane-permeabilizing activity, whereas Pa(2-19) showed poor membrane-binding and permeabilizing activities. The results indicate that the basic residue at the N-terminal is essential for the membrane-binding activity of parasin I, and among the membrane-binding parasin I analogs, the a-helical structure is necessary for the membrane-permeabilizing activity. (C) 2008 Elsevier Inc. All rights reserved.